P4.108 Increasing hiv testing of emergency department (ED) patients with increased risk for hiv and their partners and peers through provision of home hiv self-testing kits and linkage to internet-based recruitment for hiv testing – a pilot randomization study of a novel ed intervention. (8th July 2017) - Hsieh, Yu-Hsiang; Patel, Anuj V; Rothman, Richard E; Kim, Angie S; Jett-Goheen, Mary; Signer, Danielle; Latkin, Carl A; Gaydos, Charlotte A
Abstract : Introduction: Many emergency department (ED) patients with significant risks for HIV accept testing when offered in the ED but otherwise do not test for HIV on a regular basis. EDs could potentially serve as a portal for increasing HIV testing for this population beyond the ED. We conducted a pilot study to determine the acceptability of home HIV self-testing (HIVST) after the ED visit. Methods: In 2016, a pilot randomised study was conducted in an urban ED in Baltimore where an HIV screening program operated. Patients who accepted ED testing and were identified as having increased risk for HIV were enrolled. Consented patients were randomised to the HIVST group (received an oral fluid HIV home test kit), or control group (received a pamphlet regarding the importance of regular HIV testing). Participants in the HIVST group were encouraged to report self-testing results using an established online HIV/STI screening website, "IWantTheKit (IWTK)". Enrollees in the HIVST group also received 5 referral cards for their partners/peers to request HIV self-testing kit from IWTK. Phone follow-up was conducted at 1 and 3 months. Increase in HIV testing proportion was estimated as a rate ratio (RR) using a chi-square test. Results: Overall, 100 patients were enrolled and randomised. At 3 month follow-up, 20 (40%) patients in the HIVST group reported testing for HIV vs. 7 (14%) in the control group [RR: 2.9 (95% CI: 1.3, 6.1) or 3.2 (1.6, 6.6) excluding 30 patients lost to follow-up]. 95% of patients in the HIVST group who reported testing for HIV used the provided kit. 9 of 19 (47%) patients who self-tested at home reported their results to IWTK. None reported a reactive result for HIV. 54% of enrollees in the HIVST group reported that they distributed referral cards to their partners/peers; 6 used the referral card to request HIV and/or STI testing kits. Conclusion: This novel approach to providing HIVST kits for home testing to ED patients could increase overall HIV testing rates for patients who are at high risk, but not regularly tested, and for their partners and peers.